373 Evaluation of next generation-distillers dried grain as a dietary ingredient in dog and cat diets. (7th December 2018) - Smith, S; Aldrich, G
Abstract: While pet foods have been shifting towards grain-free foods, the majority still utilize cereals and their protein rich co-products. Corn gluten meal (CGM), soybean meal (SBM) and distillers dried grains (DDG) have been used in pet foods for decades. A new higher protein DDG (next generation-distillers dried grains; NG-DDG) has become available and merits evaluation. Therefore, the objective of this study was to determine the effect of NG-DDG in pet diets on digestibility and stool consistency in dogs, and palatability in dogs and cats. Twelve beagle dogs were fed diets with a similar ingredient base in which NG-DDG replaced SBM or CGM. Diets were formulated to be isonutritional, contain equal amounts of protein, and were supplemented with chromic oxide to estimate apparent total tract digestibility (ATTD). The DM digestibility for the dogs fed the CGM diet was higher (P < 0.05) than those fed the SBM diet (81.13 vs. 78.78%), with dogs fed NG-DDG intermediate to both (79.90%). The dogs fed CGM had great OM ATTD (P < 0.05) than dogs fed NG-DDG and SBM (85.26 vs. average 82.64%). The dogs fed SBM had lower CP ATTD (P < 0.05) than those fed CGM and NG-DDG (80.90 vs. average 83.72%). There were no differences (P>0.05) between dietary treatment for ATTD of crude fat, crude fiber, or energy (average 90.73, 10.03, or 73.17%, respectively). Dogs fed the diet containing NG-DDG had larger (P < 0.05) fecal mass than those fed SBM and CGM and had a similar fecal score to those fed SBM, but higher (P < 0.05) than those fed diets with CGM. In palatability assessment dogs had a preference (P < 0.05) for diets containing CGM over SBM and NG-DDG, but cats showed a preference for diets containing NG-DDG (P < 0.05) over those produced with CGM. These results indicate that NG-DDG is comparable to CGM and SBM in dog and cat diets.